2018
DOI: 10.1021/acs.jpcb.8b06283
|View full text |Cite
|
Sign up to set email alerts
|

Elucidating Aggregation Pathways in the Donor–Acceptor Type Molecules p-DTS(FBTTh2)2 and p-SIDT(FBTTh2)2

Abstract: We investigated the aggregation behavior of the donor-acceptor molecules p-DTS(FBTTh) (T1) and p-SIDT(FBTTh) (H1) in MTHF solutions. Using optical spectroscopy, we found that T1 forms aggregates in solution while H1 aggregates only when processed as a thin film, but not in solution. Free energy molecular dynamics (MD) simulations based on force fields derived from quantum-mechanical density functional theory fully reproduce this difference. Our simulations reveal that this difference is not due to the lengthy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 46 publications
0
9
0
Order By: Relevance
“…[62] In the following sections, the impact of the state of aggregation in the solid state on OSC device performance is discussed for representative organic semiconductor molecules. In literature, aggregation effects in OSCs have been reported for molecules bearing benchmark chromophore backbones including diketopyrrolopyrroles (DPPs), [63,64] boron-dipyrromethenes (BODIPYs), [65,66] perylene dye oligomers (PBIs/PDIs), [67,68] D-A-D, [69,70] and acceptor-donor-acceptor (A-D-A) [71,72] dyes, or even polymers. [73,74] In most cases, however, a lack of sophisticated theoretical investigations and crystallographic data prevents an in-depth understanding of the aggregation mode and its effects on optical properties in solid state and the corresponding device properties.…”
Section: Organic Solar Cellsmentioning
confidence: 99%
“…[62] In the following sections, the impact of the state of aggregation in the solid state on OSC device performance is discussed for representative organic semiconductor molecules. In literature, aggregation effects in OSCs have been reported for molecules bearing benchmark chromophore backbones including diketopyrrolopyrroles (DPPs), [63,64] boron-dipyrromethenes (BODIPYs), [65,66] perylene dye oligomers (PBIs/PDIs), [67,68] D-A-D, [69,70] and acceptor-donor-acceptor (A-D-A) [71,72] dyes, or even polymers. [73,74] In most cases, however, a lack of sophisticated theoretical investigations and crystallographic data prevents an in-depth understanding of the aggregation mode and its effects on optical properties in solid state and the corresponding device properties.…”
Section: Organic Solar Cellsmentioning
confidence: 99%
“…In the case of trap‐assisted recombination, the impurity creates a distribution of localized energy levels in the bandgap at which one charge carrier gets trapped and then recombines with the respective free charge carrier of the opposite sign. [ 35,38–41 ] According to the Shockley‐Read‐Hall statistics, trap‐assisted recombination losses are most detrimental for the device performance in the case of deep traps that are located near the midgap of the semiconductor, facilitating efficient recombination through the trap‐states. [ 40,41 ]…”
Section: Introductionmentioning
confidence: 99%
“…The situation should become clearer if one considers a usually closely related event, i.e., aggregation. Gekle’s group has recently conducted in-depth computational studies on the solutions of perylene bisimide (PBI) and a donor–acceptor type of small molecules . They found that solvation shell removal and the (kinetic) energy barrier involved play an important role in the transition to π–π packing, and the solvation shell rigidity (or stability) was noted to impact the free-energy curve (or PMF) at intermediate separation distances.…”
Section: Resultsmentioning
confidence: 99%
“…Intriguingly, the results seem to be at odds with the usual expectation that increasing the side-chain length of P3ATs would, for instance, reduce the well depth to discourage chain association and thus improve their solubility. Gekle’s group has previously shown that the side-chain units of the donor–acceptor type of small molecules play little or no role in improving the solubility . De Pablo’s group and Caddeo and Mattoni have also suggested that there are yet subtleties concerning the general impact of side-chain units that demand further investigations.…”
Section: Resultsmentioning
confidence: 99%